First description of movement and ranging behavior of the Griffon vulture (Gyps fulvus) from Serbia using GPS satellite tracking - Hribšek, Irena; Plećaš, Milan; Skorić, Stefan; Marinković, Saša (Archives of Biological Sciences, 2021)
Paper description: Understanding the ranging behavior of Eurasian Griffon vulture populations is fundamental for their conservation. In Serbia in 2011 for the first time, an immature Eurasian Griffon vulture was equipped with a satellite transmitter, and telemetry data, its ranging behavior, changes in foraging area, home-range, core and basic areas were followed for 3 years. The used area was larger during spring and summer; 1 basic area and its associated core area around the Uvac colony and 3 additional core areas in its proximity were identified. Ranging behavior mapping provides information for spatial planning of conservation measures. Abstract: Understanding the movement pattern and ranging behavior of the Griffon vulture population in Serbia is of great importance for prioritizing conservation action. In 2011, an immature vulture was the first bird to be equipped with a satellite transmitter in Serbia. Our study aims to define the vulture’s foraging areas, home ranges, core and basic areas, and to investigate movement patterns across different years and seasons by analyzing satellite telemetry data. We tracked the movements of the vulture for over three years and obtained satellite tracking data for 34 bird-months (1976 GPS fixes) between October 2011 and July 2014. We determined that the overall foraging area of the vulture across the entire study period was 11654.34 km2. The overall area used by the vulture was larger during spring and summer than during winter periods. Combined ranges across all years identified one basic area and its associated core area around the Uvac colony and nearby feeding site; we identified three core areas in its proximity. This study showed that areas of traditional stock-raising practices are important vulture foraging areas and that supplementary feeding sites have a vital role. Our maps can be used for future planning of vulture conservation measures.